BEYOND COMPARISON: HIGHLIGHTING THE GAP SIMILARITIES IN DUOLINGO AND ENGLISHSCORE TESTS - Samsul Khabib; Rarasaning Satianingsih; Nur Rohmah (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The Duolingo English Test (DET) and the British Council’s EnglishScore are gaining popularity as alternative digital English tests. Previous research has tended to compare the strengths of both platforms, but has rarely identified patterns of weaknesses that users may share, albeit with varying degrees of severity. This study aims to explore and thematically compare the weaknesses reported by DET and EnglishScore users in the Indonesian EFL context. The study used a qualitative approach with thematic analysis (Braun & Clarke, 2006) of open-ended comments from two independent surveys. A total of 129 DET users and 133 EnglishScore users (total N=262) – Teacher Professional Education program students at a private university in Surabaya – completed a user experience questionnaire, including open-ended questions about the most difficult parts to understand. The analysis yielded six themes of weaknesses that emerged across both platforms: (1) unclear or confusing instructions; (2) technical stability issues (crashes/self-exiting); (3) audio/speaking issues (voice detection and speed); (4) too short a turnaround time; (5) difficulty for English beginners; and (6) lack of specific feedback. Although the frequency of complaints was significantly higher on DET, the pattern of weaknesses experienced was qualitatively the same across both platforms. Digital English language testing platforms, regardless of their performance level, face similar functional challenges. Developers need to prioritize improvements in instruction clarity, technical stability, and accessibility for users with low English proficiency. This research contributes to the literature on user experience evaluation of digital assessment platforms in developing countries.